2017
DOI: 10.1111/ene.13348
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal immunoglobulin synthesis in patients with symptomatic epilepsy and epilepsy of unknown etiology (‘cryptogenic’)

Abstract: Intrathecal IgG synthesis/OCBs were observed slightly more frequently in patients with 'cryptogenic' epilepsy and with first seizures of unknown etiology than in other patient groups. However, this remained an infrequent finding and thus we could not confirm humoral immunity as a leading disease mechanism in patients with epilepsy in general or with unknown etiology in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…An immune mediated mechanism has been suggested in some epilepsy types [21]. While Kowski et al reported a high incidence of intrathecal immunoglobulin synthesis in patients with so far classified cryptogenic epilepsy (34.1%), Fauser and colleagues detected intrathecal immunoglobulin synthesis only in 8% patients with epilepsy of unknown origin, and in 5% of patients with first seizures of unknown cause, and concluded that the findings were too infrequent and not indicating a leading humoral pathomechanism [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…An immune mediated mechanism has been suggested in some epilepsy types [21]. While Kowski et al reported a high incidence of intrathecal immunoglobulin synthesis in patients with so far classified cryptogenic epilepsy (34.1%), Fauser and colleagues detected intrathecal immunoglobulin synthesis only in 8% patients with epilepsy of unknown origin, and in 5% of patients with first seizures of unknown cause, and concluded that the findings were too infrequent and not indicating a leading humoral pathomechanism [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the difference in Ig detection may be the unselective indication for lumbar puncture in the above‐mentioned study. Another reason may be the difference in laboratory methods, since OCB analysis was performed via silver staining in the above‐mentioned study, as suggested by Fauser et al in a different context …”
Section: Discussionmentioning
confidence: 96%
“…Consistent with our findings of 5%, Fauser et al . found intrathecal IgG synthesis in 4–8% of their patients not related to seizure etiology (cryptogenic, symptomatic, idiopathic) using immunoblot for OCB detection. In contrast, Kowski et al .…”
Section: Discussionmentioning
confidence: 99%
“…patients with infectious encephalitis) in the above‐mentioned study. Methodical differences between the studies also have to be considered (silver staining versus more specific immunoblot) .…”
Section: Discussionmentioning
confidence: 99%